Sources and determinants of discretionary food intake in a cohort of Australian children aged 12–14 months - Coxon, Claire; Devenish, Gemma; Ha, D.; Do, L.; Scott, Jane (MDPI, 2020)
Despite recommendations to the contrary, consumption of discretionary (energy-dense, nutrient-poor) foods begins for some children early in the weaning period, and the proportion of children consuming discretionary foods increases markedly in the second year of life. The purpose of this study was to determine intake and sources of discretionary foods in a cohort of 828 Australian toddlers (mean age: 13.1mo), and to identify determinants of discretionary food intake. At approximately 12 months of age, 3 non-consecutive days of dietary intake data were collected using a 24-h recall and 2-day food record, and the percentage total energy derived from discretionary foods was estimated. Linear regression was used to identify associations between discretionary food intake and socio-demographic determinants (mother’s age, level of education, country of birth, pre-pregnancy body mass index, socioeconomic position, parity, age of child when mother returned to work, and child’s sex) and age at which complementary foods were introduced. The average energy intake of children in this cohort was 4040 (±954.7 SD) kJ with discretionary foods contributing an average of 11.2% of total energy. Sweet biscuits, and cakes, muffins, scones and cake-type desserts contributed 10.8% and 10.2% of energy intake from discretionary foods, respectively. Other key contributors to energy intake from discretionary foods included sausages, frankfurters and saveloys (8.3%), vegetable products and dishes where frying was the main cooking technique (8.6%), butter (7.3%), and finally manufactured infant sweet or savory snack foods (9.3%). Higher intakes of discretionary food were associated with children having two or more siblings (p = 0.002), and being born to younger mothers (<25 years) (p = 0.008) and mothers born in Australia or the United Kingdom (p < 0.001). Parents, in particular young mothers and those with larger families, need practical guidance on how much of, and how often, these foods should be eaten by their children.